2004
DOI: 10.1093/ndt/gfh075
|View full text |Cite
|
Sign up to set email alerts
|

Socio-personal profile of teenagers opposed to organ donation

Abstract: The profile of the teenager who is opposed to organ donation is one who has only primary schooling or who left school early, is not engaged in pro-social activities, rejects cadaver manipulation and has no knowledge of the brain death concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 11 publications
1
49
1
11
Order By: Relevance
“…It is difficult to explain this attitude, but it raises the question of whether the first answer given about attitude towards donation was due to the need to please and whether they really do have such a positive opinion. With respect to psychosocial factors that determine this attitude, we have found that most classic psychosocial factors in the population do not have an influence (6)(7). What does in fact determine attitude are family factors: family communication on issues about donation and transplantation as well as partner's or spouse's opinion about organ donation.…”
Section: Discussionmentioning
confidence: 93%
“…It is difficult to explain this attitude, but it raises the question of whether the first answer given about attitude towards donation was due to the need to please and whether they really do have such a positive opinion. With respect to psychosocial factors that determine this attitude, we have found that most classic psychosocial factors in the population do not have an influence (6)(7). What does in fact determine attitude are family factors: family communication on issues about donation and transplantation as well as partner's or spouse's opinion about organ donation.…”
Section: Discussionmentioning
confidence: 93%
“…All the rates are similar and sometimes higher than those found in the general public in favor of deceased-donor donation. 15,16 Second, living donation has positive effects on the donor (it does not just cause morbidity and mortality) but an improvement in the personal relationship between donor and recipient. 17 This means that there is a strong potential supply of organs far above that of deceased-donor organs that has yet to be developed in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In other words, respondents are much more in favor when they believe that they might be potential recipients of a transplant and when they would be willing to receive one from a living donor.…”
Section: Figure 1 Attitude Toward Living-organ Donation According Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Bu farkın hangi yaş gruplarından kaynaklandığı incelendiğinde, 25 yaş altı ve 25-35 yaşları arasında yer alan öğretmenlerin 36-45 yaş aralığı ve 46 yaş üzeri öğretmenlere nazaran daha olumlu tutum sergilemelerinden kaynaklandığı ortaya çıkmıştır. Bu sonuç, Conesa et al (2004), Öztürk ve vd. (2009Öztürk ve vd.…”
Section: Tartişma Ve Sonuçunclassified